Amino-Functionalized Mesoporous Silica Nanoparticle-Encapsulated Octahedral Organoruthenium Complex as an Efficient Platform for Combatting Cancer - Gounko, Iouri (American Chemical Society (ACS), 2020)
In the process of synthesis of a new drug, as important as the drug itself is the formulation used, because the same compound can present a very different efficacy depending on how it is administered. In this work, we demonstrate how the antitumor capacity of a new octahedral organoruthenium complex, [Ru(ppy-CHO)(phen)2][PF6] is affected by its encapsulation in different types of mesoporous silica nanoparticles. The interactions between the Ru complex and the silica matrix and how these interactions are affected at two different pHs (7.4 and 5.4, mimicking physiological and endolysosomal acidic conditions, respectively) have been studied. The encapsulation has also been shown to affect the induction of apoptosis and necrosis and progression of the cell cycle compared to the free drug. The encapsulation of the Ru complex in nanoparticles functionalized with amino groups produced very high anticancer activity in cancer cells in vitro, especially against U87 glioblastoma cells, favoring cellular internalization and significantly increasing the anticancer capacity of the initial non-encapsulated Ru complex.
PUBLISHED
Keywords: Apoptosis; Cell Line; Tumour